Mobile devices in lifelong learning: setting a research agenda - Balula, Ana (2019)
Aiming at bridging the gap in research documenting the use of mobile devices in promoting informal lifelong learning, this paper set out to develop an in-depth literature review based on current research within this scope. Drawing on the themes of educational change highlighted in the NMC Horizon Report: 2017 Higher Education Edition, a benchmark in the exploration of emerging technology trends in education, it focuses on open access research published within the last two years (2017-2018). This thorough review has established that, in addition to a growing fluidity, the transition between formal and informal learning is paving the way for the reconceptualization of pedagogical approaches, both on a personal and institutional level. Based on the literature, the use of mobile learning has mostly impacted employability and workplace, the development of agile learning ecosystems and the emergence of new learning cultures. Considering the growing relevance of the topic, future research should continue to tackle these issues and address some of its constraints. The review also indicates that it is key to carry out research on the role educational institutions will play within this setting.